2013
DOI: 10.1039/c2tb00025c
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer functionalized reduced graphene oxide with enhanced biocompatibility via mussel inspired coatings/anchors

Abstract: A green and facile method for preparing biopolymer functionalized reduced graphene oxide (RGO) by using mussel inspired dopamine (DA) as the reducing reagent and the functionalized molecule is proposed. In the study, GO is reduced by DA and DA is adhered to RGO by one-step pH-induced polymerization of DA (polydopamine, PDA), and then heparin or protein is grafted onto the PDA adhered RGO (pRGO) through catechol chemistry. The obtained pRGO, heparin grafted pRGO (Hep-g-pRGO), and BSA grafted pRGO (BSA-g-pRGO) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(175 citation statements)
references
References 53 publications
(64 reference statements)
6
169
0
Order By: Relevance
“…Our studies are consistent with previous reports demonstrating that biopolymer-functionalized rGO exhibits an ultralow hemolysis ratio and significant cytocompatibility in human umbilical vein endothelial cells, even at a high concentration of 100 μg/mL. 29,41 Altogether, these data suggest that graphene can be intrinsically nontoxic, with its toxicity potential only appearing after chemical treatment or increased concentration, incubation time, or size. Besides these factors, surface functionalization is an alternative and suitable approach to improve the biocompatibility of nanomaterials for safer biomedical applications.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our studies are consistent with previous reports demonstrating that biopolymer-functionalized rGO exhibits an ultralow hemolysis ratio and significant cytocompatibility in human umbilical vein endothelial cells, even at a high concentration of 100 μg/mL. 29,41 Altogether, these data suggest that graphene can be intrinsically nontoxic, with its toxicity potential only appearing after chemical treatment or increased concentration, incubation time, or size. Besides these factors, surface functionalization is an alternative and suitable approach to improve the biocompatibility of nanomaterials for safer biomedical applications.…”
Section: Discussionsupporting
confidence: 81%
“…No toxicity was observed when cells were exposed to doses 100 μg/mL of functionalized rGO. 41 The water-soluble oxidized graphene nanoribbons mixed with PEG-DSPE (1,2-distearoylsn-glycero-3-phosphoethanolamine-N-[amino(polyeth ylene glycol)]) showed significantly different cytotoxic profile compared to graphene nanoparticles. 42 The effects of various two-dimensional graphene nanostructures such as graphene nano-onions, graphene oxide nanoribbons, and graphene oxide nanoplatelets on cell viability and differentiation were evaluated with human mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The biopolymer functionalized rGO exhibits an ultralow hemolysis ratio and good cytocompatibility in human umbilical vein endothelial cells (HUVECs), even at a high concentration of 100 µg/ mL. 67 they exhibited excellent in vitro cytocompatibility within a concentration of 100µg/mL, especially for CS-GO-HA.…”
Section: The Effect Of Lower Concentrations Of Tea-rgo On Proliferatimentioning
confidence: 99%
“…Cheng et al 31 observed that biopolymer functionalized rGO exhibits an ultralow hemolysis ratio and good compatibility in human umbilical vein endothelial cells, even at a high concentration of 100 µg/mL. Heparinfunctionalized rGO has been shown to have good stability in aqueous solution, owing to the strong electrostatic and steric repulsions of the heparin, which adsorb on the surfaces of rGO sheets.…”
Section: Cell Mortalitymentioning
confidence: 99%
“…Thus, as many of the currently available methods for producing graphene are not environmentally friendly, complicated, and require additional steps in the preparation process that restrict their applications in biological and biomedical fields, 31 we developed a novel, cost-effective, simple, environmentally friendly approach to produce water-soluble graphene. Further, we examined the toxicity of the biologically reduced graphene oxide (B-rGO) in MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%